Analisis Kepuasan Pelanggan dalam Membeli Buah-buahan Segar di Moena Fresh Bali - WARDIKA, PUTU OKA; DEWI, RATNA KOMALA; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018, 2018)
Analysis Customer Satisfaction in Buying Fresh Fruits in Moena Fresh Bali Increased consumption of fruits in the country have an impact on the growth of fruit sales in Indonesia. This increase causes the appearance of stiff competition in the business of fruits. Moena Fresh Bali as one of the companies that sell fresh fruits must innovate or improve the shortage so that the consumers do not turn to other products. Consumer behavior may help explain how consumers obtain satisfaction. The purpose of this research is to determine satisfaction of Moena Fresh Bali consumers and to find out actions to increase customer satisfaction of Moena Fresh. The location of the research was conducted at four Moena Fresh outlets as it was considered to represent consumers in every sub-district in Denpasar City. The number of respondents was as many as 50 respondents and the sampling was conducted by using accidental sampling. Types of data collected include quantitative and qualitative data which were sourced from primary and secondary data. Methods of data collection were by using interview techniques, observation, and documentation. Data analysis methods used were descriptive analysis, Importance Performance Analysis and Customer Satisfaction Index. Based on the results of research, the calculation of CSI to the attributes of Moena Fresh Bali was 77.6% i.e. it meets the criteria of satisfaction. Based on the Matrix of Importance Performance, product attributes are classified into four quadrants and actions to improve customer satisfaction are through the improvement of attributes that become the main priority, namely the attributes of advertising / promotion, price, and discounts. The study suggests that Moena Fresh Bali should perform printed and electronic publications and set competitive prices to maintain its customers.